2020
DOI: 10.1159/000507434
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aging on the Characterization of Brown and White Adipose Tissue-Derived Stem Cells in Mice

Abstract: Adipose tissue enriched with adipose tissue-derived stem cells (ASCs) is often used for stem cell-based therapies. However, the characteristics of ASCs from different types of adipose tissue have varying biochemical and functional properties. We aimed to investigate how age affected the biological and functional characteristics of ASCs from brown (BAT) and white adipose tissue (WAT). ASCs were obtained and cultured from mouse BAT and WAT at different ages: young (2 months of age) and older mice (22 months of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…71,72 We also observed that the expression of CITED1 and PGC1-α was significantly higher in MSCs derived from beige deposits of the inguinal fat pad than in white ones, which suggests a greater commitment of MSCs with the differentiation of thermogenic beige adipocytes in the bMSCs than WMSCs. This could be explained by the epigenomic memory found in beige adipocytes, 46 which could be present in BAT and explain similar data obtained in mice 73 and human studies 60,74,75 in which derived MSCs from BAT were found to express higher levels of thermogenic proteins. A long-term cold exposure study in mice revealed that de novo beige biogenesis was favored from adipogenic precursor cells, 76 suggesting that the beige biogenesis mechanism, either by darkening of pre-existing mature adipocytes or de novo differentiation, also depends on the frequency and duration of stimuli such as cold.…”
Section: Papersupporting
confidence: 69%
“…71,72 We also observed that the expression of CITED1 and PGC1-α was significantly higher in MSCs derived from beige deposits of the inguinal fat pad than in white ones, which suggests a greater commitment of MSCs with the differentiation of thermogenic beige adipocytes in the bMSCs than WMSCs. This could be explained by the epigenomic memory found in beige adipocytes, 46 which could be present in BAT and explain similar data obtained in mice 73 and human studies 60,74,75 in which derived MSCs from BAT were found to express higher levels of thermogenic proteins. A long-term cold exposure study in mice revealed that de novo beige biogenesis was favored from adipogenic precursor cells, 76 suggesting that the beige biogenesis mechanism, either by darkening of pre-existing mature adipocytes or de novo differentiation, also depends on the frequency and duration of stimuli such as cold.…”
Section: Papersupporting
confidence: 69%
“…The isolation and culture of W-ASCs and B-ASCs have been previously described. 9 The mice were anesthetized, and WAT was removed from the groin and BAT from the scapula with sterile surgical scissors and forceps after washing with phosphate buffered saline. After digestion, DMEM/F12 (Fisher Scientific, 8,115,296) medium containing 10% fetal bovine serum (Fisher Scientific, 1,715,752) was added, after the tissue was passed through a 70 μm screen (BD Bioscience), the cells were centrifuged at 300 g for 5 min and the supernatant was discarded.…”
Section: Isolation and Culture Of W-ascs And B-ascsmentioning
confidence: 99%
“…The numbers of senescent cells and the rate of apoptosis of ASCs were significantly higher in old compared with young mice, and osteogenic and adipogenic differentiation capacity were decreased. 9 Previous studies have reported the osteogenic differentiation of ASCs in young mice 9,10 and that the intravenous injection of fat-derived stem cells with autologous ASCs effectively regulated the blood and biochemical parameters, renal function, and antioxidant enzyme activity of elderly rats. 10 In this study, intraperitoneal injection of white adipose stem cells (W-ASCs) in young mice reduced the gain in body weight observed in old mice, increased the levels of antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT), and decreased the levels of inflammatory factors such as tumor necrosis factor (TNF-α) and interleukin-6 (IL-6).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been reported that the potential ability of differentiation and tissue repair of elderly ASCs is reduced, which limits the transplantation effects (18). Our previous research has also confirmed these declines in aged mice (10), so we selected young mice as the source of donor ASCs.…”
Section: Discussionmentioning
confidence: 85%